(untitled) (Scientific journal of the Fergana State University, 2025)
Lithium hydroxide was used to improve the quality of Surkov material, and six samples of Surkov material were obtained. Each sample was tested to determine kinematic viscosity and melting temperature at temperatures of 20, 40, and 100 °C. According to the indicators of kinematic viscosity and melting temperature, the SM-4 sample showed the best results compared to the other Surkov material samples. In terms of flash point, the SM-2 and SM-4 samples exhibited higher values than the other samples. Based on the obtained results, it is recommended to use the SM-2 and SM-4 samples in the rapidly rotating parts of machinery.